Direct excitation strategy for radical generation in organic synthesis. (23rd April 2021) - Sumida, Yuto; Ohmiya, Hirohisa
Abstract : This tutorial review encompasses the radical generation based on classical methods and photoredox catalysis. It will also focus on radical generation only demanding visible-light, which involves EDA complex and direct photo-excitation strategy. Abstract : Visible-light-mediated chemical processes have been vigorously studied and have led to state-of-the-art synthetic chemistry since they enable the control of radical generation and excited-state-based transformations. The essential process is the generation of a radical species via single electron transfer (SET) between the substrate and catalyst. While photoredox chemistry is an important methodology, these systems essentially require photocatalysts and involve redox processes of the catalyst in the catalytic cycle, which often complicates the reaction. Hence, a seminal contribution in the area of photoredox chemistry is the development of a system free of a photoredox catalyst. In this tutorial review, we summarise the chronology of C-centred radicals, including photoredox chemistry, and shed light on the direct excitation strategy that enables the generation of radical species without exogenous photocatalysts. This strategy provides more straightforward methods, which are energetically efficient in principle, with the potential to open a new window into organic synthesis.